The Position of Islamic Education According to the National Educational System in Indonesia - Firman Mansir (Universitas Muhammadiyah Malang, 2022)
Education is a part of the region that requires state participation to be properly optimized. Meanwhile, educational meetings with state power always end in the use of education in the name of the interests of power. Islamic Education as a subsystem of National Education in Indonesia is an important part that cannot be separated. The linkage between education and state power can be seen as well as the linkage between institutions in society and state organizers. Educational institutions in their form in the form of schools, madrasahs, and pesantren eventually intersect with state power. The implementation of Islamic education concerns education management so that system changes can undergo changes and determine the direction of Indonesia's education policy. This research uses qualitative methods. In collecting data through literature study studies, by collecting various literature spread from various journals and research books, which are then analyzed descriptively analytically. Thus, Islamic education has become the axis of state power in the field of education, it can even determine whether the country is progressing or not resting on the quality of Islamic education represented by madrasahs and Islamic boarding schools, and other Islamic educational institutions.